Performance comparison of high temperature sensor based on non‐adiabatic silica microfiber and single mode‐multimode‐single mode fiber structure - Yusof, Nur Hotimah; Razak, Hashim Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (John Wiley & Sons, 2019)
A fiber-based temperature sensor operating at high temperature was demonstrated using multimode interference effect and its performance was compared with that of two different probes based on a non-adiabatic microfiber and singlemode-multimode-singlemode (SMS) fiber structure. Interference fringes of the output red-shifted as the temperature increased due to the change in the effective refractive index of the multiple modes inside both structures. The sensor probes were able to measure the temperature variation up to 400°C with a linearity of more than 90%. The temperature sensitivity of the microfiber and SMS sensors is 6.0 pm/°C and 11.1 pm/°C, respectively. Our proposed sensors are simple, relatively cheap to be fabricated, and could operate at high temperatures above 300°C.